Optimization of serum free medium for the production of humanized anti-cea monoclonal antibody. - Ab Latif, Nurzila (2011)
The humanized monoclonal antibody (mAb) against the colon and ovarian cancer cells has been successfully expressed in NS0 cell line. This humanized mAb can be used to detect and treat human colorectal cancer. Historically, medium supplemented with serum were widely used in animal cell culture. However, the used of serum may leads to virus and prion contamination and gives problems for the downstream process due to its unknown and undefined component. The aim of this study is to develop a suitable serum free culture medium for the production of the humanized mAb. Two types of basal medium, DMEM and IMDM were tested as suitable basal medium for the growth of NS0 cell. Cells were cultured in both basal medium supplemented with different concentration of fetal bovine serum (FBS) (1, 3, 5, 7, 10 (v/v)), 4mM of L-glutamine and 10 μg/ml of antibiotic. The cell concentration and viability of the NS0 cells were determined using tryphan blue exclusion method and ELISA was used to determine the mAb titers of the cultures. The results showed that the higher growth and mAb productivity were observed in DMEM supplemented with 10 % (v/v) FBS. The concentration reached 4.76 x 106 cells/mL compared to only 1.95 x 106 cells/mL in IMDM supplemented with 10 % (v/v) FBS medium. The highest antibody titer, 12.89 μg/ml, was obtained from culture condition of DMEM supplemented with 7 % (v/v) FBS. The other objective of this study is to optimize a serum free medium for the NS0 cell line. Different ratios of DMEM/Ex-cell medium were studied. Results showed that the most suitable ratio for the cell line to grow and producing antibody is in 5:5 DMEM/Ex-cell medium. In order to replace serum in cell culture medium, three component; insulin, SyntheChol and L-glutamine were tested using design of experiment (DOE). By using the 2 level factorial design screening method, the significant of the parameters are determined. Then further optimization was done using Central Composite Design (CCD) by augmenting the previous design using 8 additional runs. Experiments were done in T-flask with working volume of 5 mL. Results showed that several combinations gave good but not an optimum result for the responses. This is due to the narrow ranges of parameters that have been used during experimenting. A larger scale of culture (50 mL) using the optimize condition suggested by the software has substantially increased the viable cell concentration and antibody production by 75 % and 48 %, respectively compare to the non-optimal condition.